Sierra Leone : First Review Under the Extended Credit Facility Arrangement, Request for Modification of Performance Criteria, and Financing Assurances Review-Staff Report; and Press Release. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Sierra Leone's First Review Under the Extended Credit Facility (ECF) Arrangement, Request for Modification of Performance Criteria (PC), and Financing Assurances Review. Program performance has been strong. All PCs were met with comfortable margins, and all indicative targets (ITs) were met, except for the one on poverty-related spending that was missed owing to enhanced monitoring of domestic investment execution and delayed budget support. Economic growth momentum continued in 2013, with output expanding by 20 percent. The IMF staff recommends completion of the first review under the ECF arrangement.